2001
DOI: 10.1038/sj.ejcn.1601153
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge and food intake of seven-year-old children in an atherosclerosis prevention project with onset in infancy: the impact of child-targeted nutrition counselling given to the parents

Abstract: Objective: To compare nutrition knowledge and food intake in 7-y-old intervention and control children in an atherosclerosis risk factor intervention trial after 6.5 y of nutrition counselling given to the parents. Design, subjects and methods: Intervention families in the Special Turku Coronary Risk Factor Intervention Project received child-oriented nutritional counselling one to three times a year since child's age of 7 months, aimed at reduced saturated fat and cholesterol intake. Children's nutrition know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
2
17
0
1
Order By: Relevance
“…These results reveal a gap between knowledge and behaviour in Tehranian adolescents, as reported in other countries 8,19,20 . Findings from a study on Tehranian adults also indicated a sizeable gap between nutritional knowledge and behaviour 21 .…”
Section: Discussionsupporting
confidence: 70%
“…These results reveal a gap between knowledge and behaviour in Tehranian adolescents, as reported in other countries 8,19,20 . Findings from a study on Tehranian adults also indicated a sizeable gap between nutritional knowledge and behaviour 21 .…”
Section: Discussionsupporting
confidence: 70%
“…This study shows that in spite of a child-targeted, repeated nutrition counselling given to the parents during the previous 6.5 y, children's nutrition knowledge and ability to explain choices in nutrition knowledge test differed only slightly between the intervention children and the control children at the age of 7 y. Indeed, this was rather unexpected, as we have previously shown that the intervention children had low saturated fat, high unsaturated fat foods readily available at home (Lagström et al, 2001;Räsänen et al, 2001), and they also had lower saturated fat and cholesterol intake (Lagström et al, 1997) and lower serum cholesterol concentrations than the control children throughout the first years of life (Niinikoski et al, 1996;Cullen et al, 2000). Also the intervention mothers have probably been excellent role models in food selection for their children.…”
Section: Discussionmentioning
confidence: 51%
“…The intervention children have continuously had lower intake of saturated fat and cholesterol than the control children (Lagström et al, 1997). Nutrition counselling resulted in an increased intake of low-fat-and high unsaturated-fat-containing foods in the 5.5-to 7-y-old children, but it failed to influence children's sodium intake as well as scores in a nutrition knowledge picture test at the age of 7 y (Räsänen et al, 2001). The difference in serum cholesterol concentration between the intervention and control children has been between 3 and 10% during the follow-up (Lapinleimu et al, 1995, Niinikoski et al, 1996Rask-Nissilä et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the association between nutritional knowledge and dietary intake has been found in several studies (6)(7)(8)(9)(10) . Moreover studies examining the effects of programmes designed to increase nutrition knowledge have found positive results (11,12) . However, other studies found no significant relationship (13,14) .…”
mentioning
confidence: 99%